Thermal Characterization of p-Cresol-Urea-Formaldehyde Terpolymer Resins - Aram1, S.; Karunakaran2, M.; Vijayakumar3, C.T. (Asian Journal of Chemistry, 2013)
Terpolymer resin was synthesized through the condensation of p-cresol, urea and formaldehyde in the mole ratio 1:1:2 in the presence of 2 M HCl as the catalyst. The weight average molecular weight of the synthesized terpolymer was found to be 8738 as determined by gel permeation chromatography. The structure of the terpolymer was investigated using fourier transform infrared spectrophotometer and proton nuclear magnetic resonance spectrometer (1H NMR). Thermogravimetric analysis was performed to establish its thermal stability. Doyle, Horowitz and Metzger, Murray and White, Broido and Dharwadkar and Kharkhanavala methods were used to calculate the thermodynamic parameters such as enthalpy of activation (H*), entropy of activation (S*), free energy of activation (G*) and pre-exponential factor (A) for the different thermal decomposition steps shown by the terpolymer.